ChemInform Abstract: Facile Synthesis of Pyrroles via Rh(II)‐Catalyzed Transannulation of 1‐Tosyl‐1, 2, 3‐triazoles with Silyl or Alkyl Enol Ethers. Issue 15 (April 2015) - Feng, Juan; Wang, Yuanhao; Li, Qingong; Jiang, Renwang; Tang, Yefeng
Abstract: The title reaction proceeds with high regioselectivity and provides a wide range of substituted pyrroles.